Exploring the Role of Selected Bacterial Strains in Chromium (Cr(VI) Reduction from Soil - Singh, Rachna; Gupta, Mahendra K. (International Journal of Scientific Research in Biological Sciences, 2019)
World’s rapidly evolving population and its progressive attraction towards luxurious life has unsurprisingly led to an increase in anthropogenic sources of pollution. Environmental contamination of hexavalent chromium Cr(VI) is of serious concern for its toxicity as well as mutagenic and carcinogenic effects. Bacterial chromate reduction is a cost-effective technology for detoxification and removal of Cr(VI) from polluted environment. In current study, a total of 15 Cr(VI) resistant bacterial isolates were isolated after enrichment at three different Cr(VI) concentrations- 25mg/L, 50 mg/L and 100 mg/L. Out of 15 only three- S1B, S10D and S3-A with a maximum tolerance of 100mg/L Cr(VI) concentration were selected for further study. On the basis of biochemical characterization isolates were identified, S1-B as Enterococcus faecalis, S10-D as Bacillus megaterium and S3-A as Bacillus cereus. Efficiency of chromium reduction by selected isolates was evaluated at optimized growth conditions. All the three isolates have shown excellent chromium reduction with 100% by S10D, 78.6 % by S1B and 61.36% by S3-A at 25mg/L of Cr(VI) concentration. All three isolates had shown around 60% reduction within 48 h of incubation period. Multimetal resistance was also determined against six different heavy metals (Hg, Cd, Pb, Zn, Co, Mn). Cd and Hg were highly toxic and supressed the bacterial growth completely, only S10D was resistant to Cd. S2D, S3A and S10D were resistant against Co, Pb and Mn while growth of S3A was inhibited by Zn. These potential bacterial isolates could be used at industrial level for effluent treatment and also have great significance for bioremediation of chromium contaminated sites.